Penyusunan Tata Kelola Audit E-Procurement Instansi Pemerintah - Rendra Papang Eko Noor Sancoyo; Eko Nugroho (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
E-procurement is a new electronic procurement system which implemented by governmental departments. It is expected to reduce irregularities in governmental procurement that can lead to loss of financial state. The way to ensure that eprocurement aligned with the development goals is audit. Audit needs an audit program which help auditors to conduct their audit procedures. Today, an e-procurement audit program for governmental departments is not available. This research designs an audit program for governmental e-procurement based on COBIT 5 activities. These activities are used to determine the audit scopes. The respondents who choose COBIT 5 activities are the LPSE team at Provinsi Banten and the Audit Board of the Republic of Indonesia auditors. The result of this study shows that the e-procurement audit program consists of the audit scope, audit objectives, and activities in planning, implementation, and completion. The audit scope, audit objectives, and activities in implementation are concluded based on COBIT 5 fifteen process that selected by respondents. Planning and completion activities are determined based on audit program literature.